Creating a Healthy Generation : PAUD Principal’s Strategy in Creating Clean and Healthy Living Habits - Mahyuni; Syarfina, Syarfina; Lestari, Suci; Adelia, Putri (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR.KH.EZ.Muttaqien Purwakarta, 2024)
This study examines the strategies the head of early childhood institutions applied in implementing Clean and Healthy Living Behavior in children aged 5-6. The method used in this research is qualitative, which is analyzed descriptively. The participants in this study were the head of PAUD and class B1 children aged 5-6 years, totaling 20 children at Buah Hati ECE, Langsa City, Aceh. The data were collected through observation, interview, and documentation. Data analysis techniques in this study are data collection, reduction, and conclusion drawing. The results showed that the principal applied the strategy of habituation, knowledge, and giving examples. All teachers apply the strategy, and it is influential in shaping PHBS behavior in early childhood. This research creates an ecosystem that supports children in practicing clean and healthy living behaviors at school and everyday life. Penelitian ini mengkaji strategi yang diterapkan kepala lembaga PAUD dalam menerapkan Perilaku Hidup Bersih dan Sehat pada anak usia 5-6 tahun. Metode yang digunakan dalam penelitian ini adalah kualitatif yang dianalisis secara deskriptif. Partisipan dalam penelitian ini adalah kepala PAUD dan anak kelas B1 usia 5-6 tahun yang berjumlah 20 anak di PAUD Buah Hati, Kota Langsa, Aceh. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi. Teknik analisis data dalam penelitian ini adalah pengumpulan data, reduksi, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa kepala sekolah menerapkan strategi pembiasaan, pengetahuan, dan pemberian contoh. Semua guru menerapkan strategi tersebut, dan berpengaruh dalam membentuk perilaku PHBS pada anak usia dini. Penelitian ini menciptakan ekosistem yang mendukung anak dalam mempraktikkan perilaku hidup bersih dan sehat di sekolah dan kehidupan sehari-hari. Â